2022
DOI: 10.1007/s11356-021-17793-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 on Sustainable Development Goals and effective approaches to maneuver them in the post-pandemic environment

Abstract: In the pursuit of constructing a sustainable world for all through the instrumental seventeen Sustainable Development Goals, the COVID-19 pandemic emerged and affected the efforts concentrated on these goals. Therefore, there is a pressing need to analyze the extent of the impact that unfolded from the pandemic on each Sustainable Development Goal and further to direct the post-pandemic situation to accelerate the progress in every goal. Besides, there exists a knowledge gap in understanding the Sustainable De… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 43 publications
2
38
0
1
Order By: Relevance
“…The report also acknowledges that ongoing efforts towards access to safe drinking water and sanitation facilities (SDG 6) as well as to affordable electricity (SDG 7) have to be paced up to ensure global coverage of these basic amenities. With respect to SDG 8 dealing with ‘decent work and economic growth’ the report reiterates that the cascading effects of inflation, supply chain disruptions, emerging COVID variants and ineffective administrative policies have further impeded economic growth and recovery, similar to the findings of Elavarasan et al 2022 (Fig. 1 ).…”
supporting
confidence: 57%
“…The report also acknowledges that ongoing efforts towards access to safe drinking water and sanitation facilities (SDG 6) as well as to affordable electricity (SDG 7) have to be paced up to ensure global coverage of these basic amenities. With respect to SDG 8 dealing with ‘decent work and economic growth’ the report reiterates that the cascading effects of inflation, supply chain disruptions, emerging COVID variants and ineffective administrative policies have further impeded economic growth and recovery, similar to the findings of Elavarasan et al 2022 (Fig. 1 ).…”
supporting
confidence: 57%
“…S9). However, the existing study concluded that SDG 1 is the most affected goal by COVID-19 [11] . The difference is mainly from the definition of the impacts of COVID-19 on SDGs.…”
Section: Resultsmentioning
confidence: 98%
“…Several studies have assessed the impacts of COVID-19 on SDGs [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] . For example, the UN's 2020 annual report on SDGs showed worrisome initial impacts of COVID-19 on some specific goals and targets [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The International Labor Organization (ILO) reports that due to the COVID-19 crisis, a 14% decline in hours worked is expected in 2020, which meant a 400 million job loss compared to the 4th quarter of 2019 [135]. Low-and middle-income countries were the hardest hit, estimating a fall in working time of up to 23.3%, equivalent to 240 million jobs in the second quarter of 2020.…”
Section: Work and Economic Growthmentioning
confidence: 99%